1985
DOI: 10.1172/jci111909
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between G2m(n) immunoglobulin allotype and human antibody response and susceptibility to polysaccharide encapsulated bacteria.

Abstract: To determine whether genetic factors influence the human antibody response to polysaccharides, we correlated Ig allotypes with the concentrations of antibody to 14 bacterial capsular antigens in 130 actively immunized Caucasian adults. The 88 individuals possessing G2m(n), an allotype antigen of IgG2 subclass heavy chains, had significantly higher postimmunization antibody levels to Haemophilus influenzae type b (Hib) and 8 of 11 pneumococcal types (P < 0.05) than the 42 lacking this antigen. For Hib, pneumoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(88 citation statements)
references
References 34 publications
2
84
1
1
Order By: Relevance
“…The IgG2 subclass is the main antipolysaccharide antibody and patients with IgG2 subclass deficiency are more prone to develop pneumonia, sinusitis, and invasive pneumococcal disease (4 ). The G2m(n) allotype of IgG2 has been associated with increased susceptibility to infections with encapsulated bacteria (5 ). The link between IgG2 and phagocytosis of encapsulated bacteria is constituted by Fc␥ receptor (R) IIa, the only Fc␥ receptors that bind IgG2 (6 ).…”
Section: Streptococcus Pneumoniae and Haemophilus Influenzae Are Impomentioning
confidence: 99%
“…The IgG2 subclass is the main antipolysaccharide antibody and patients with IgG2 subclass deficiency are more prone to develop pneumonia, sinusitis, and invasive pneumococcal disease (4 ). The G2m(n) allotype of IgG2 has been associated with increased susceptibility to infections with encapsulated bacteria (5 ). The link between IgG2 and phagocytosis of encapsulated bacteria is constituted by Fc␥ receptor (R) IIa, the only Fc␥ receptors that bind IgG2 (6 ).…”
Section: Streptococcus Pneumoniae and Haemophilus Influenzae Are Impomentioning
confidence: 99%
“…constant regions of heavy or light chains of immunoglobulins. We have recently reported that the allotype of IgG-2 heavy chains, G2m(n), is correlated with the human IgG antibody response and susceptibility to polysaccharide encapsulated bacteria in Caucasians (11). Here we examine the relationship of Km allotypes, antigenic markers on kappa light chains, to the light chain distribution of the antibody response.…”
Section: Introductionmentioning
confidence: 97%
“…In infectious diseases, patients with the IGHG*bfn/*bfn diplotype(=B1/B1-cells) have a better outcome of bacterial infections as a consequence of a high production of specific bacterial antibodies especially to polysaccharide antigens (20,21) and a more favourable outcome in autoimmune juvenile chronic arthritis (22). Furthermore the IGHG*bf-n/*bf-n diplotype (=B2/B2-cells), which was infrequent in children with a family history of allergy and atopy, is common in IgG2 deficiency and in common variable immunodeficiency (23,24).…”
Section: Discussionmentioning
confidence: 99%